2008
DOI: 10.1152/jn.90262.2008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Motor Responses Are Appropriately Tuned to the Metrics of a Visuospatial Task

Abstract: Considerable research has established that rapid motor responses (traditionally called reflexes), can be modified by a subject's voluntary goals. Here, we expand on past observations using verbal instructions by defining the voluntary goal via visual target position. This approach allowed us to objectively enforce task adherence and explore a richer set of variables, such as target direction and distance, metrics that modify voluntary control and that--according to our hypothesis--will influence rapid motor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
257
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(281 citation statements)
references
References 63 publications
22
257
0
Order By: Relevance
“…He found that, although the verbal instruction did not modulate the short-latency stretch response (i.e., 25-50 ms postperturbation onset), the magnitude of the long-latency stretch response was larger when participants were instructed to resist the perturbation. Since this seminal work, similar patterns of goal-dependent modulation have been shown in many muscles, including those acting at the jaw (Johansson et al 2014), shoulder (Kurtzer et al 2014;Nashed et al 2012;Omrani et al 2013;Pruszynski et al 2008), elbow (Cluff and Scott 2013;Colebatch et al 1979;Crago et al 1976;Evarts and Granit 1976;Nashed et al 2012Nashed et al , 2014Omrani et al 2013;Pruszynski et al 2008Pruszynski et al , 2011bRavichandran et al 2013;Rothwell et al 1980;Shemmell et al 2009), wrist (Calancie andBawa 1985;Jaeger et al 1982; Lee and Tatton 1982;Manning et al 2012), finger (Capaday and Stein 1987;Cole et al 1984;Marsden et al 1981), and ankle (Gottlieb and Agarwal 1979;Ludvig et al 2007). …”
mentioning
confidence: 70%
See 1 more Smart Citation
“…He found that, although the verbal instruction did not modulate the short-latency stretch response (i.e., 25-50 ms postperturbation onset), the magnitude of the long-latency stretch response was larger when participants were instructed to resist the perturbation. Since this seminal work, similar patterns of goal-dependent modulation have been shown in many muscles, including those acting at the jaw (Johansson et al 2014), shoulder (Kurtzer et al 2014;Nashed et al 2012;Omrani et al 2013;Pruszynski et al 2008), elbow (Cluff and Scott 2013;Colebatch et al 1979;Crago et al 1976;Evarts and Granit 1976;Nashed et al 2012Nashed et al , 2014Omrani et al 2013;Pruszynski et al 2008Pruszynski et al , 2011bRavichandran et al 2013;Rothwell et al 1980;Shemmell et al 2009), wrist (Calancie andBawa 1985;Jaeger et al 1982; Lee and Tatton 1982;Manning et al 2012), finger (Capaday and Stein 1987;Cole et al 1984;Marsden et al 1981), and ankle (Gottlieb and Agarwal 1979;Ludvig et al 2007). …”
mentioning
confidence: 70%
“…If the participant's response was inaccurate (i.e., missed the target) or too slow (i.e., took longer than 375 ms to reach the target), the target color would change from white to red to indicate an error-otherwise, the target color would change from white to green ( Fig. 1D; see also Pruszynski et al 2008). Participants completed 20 trials of each of the 24 experimental conditions (3 joint segments: shoulder, elbow, wrist; 2 preloads: flexion, extension; 2 perturbation loads: flexion, extension; 2 targets: left, right) in a randomized order totaling 480 trials.…”
Section: Methodsmentioning
confidence: 99%
“…We followed classic definitions of the different epochs of time found in the literature (Crago et al 1976;Lee and Tatton 1982;Nakazawa et al 1997;Pruszynski et al 2008). The first epoch (R1) occurs from 20 to 45 ms postperturbation and is referred to as the short-latency response.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The overlap in distribution between perturbation-induced motion and the natural variability was addressed by receiver operating characteristic (ROC) analysis (Corneil et al 2004;Pruszynski et al 2008). This technique is used to compute a time series of estimates of the probability to discriminate two random variables based on their empirical distribution.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation